An application of Bayes’ theorem to a problem of Cultural astronomy interest - Adriano Gaspani; Stefano Spagocci (Cultural Heritage and Modern Technologies)
In this paper, an elliptical enclosure, found at Piani d’Avaro (Bergamo Province, Lombardy, Northern Italy) was examined from an astronomical point of view. Due to earlier studies by one of the authors (Gaspani), its internal structures were known to be astronomically aligned - and suspected to date back to the Iron Age - but the external enclosure was thought to be Late-Medieval. Using a dating algorithm, devised by the authors, it was confirmed that the site is astronomically aligned. Lunar and solar alignments are reported, among which we mention those at sunrise and sunset on the four main Celtic festivals. We found out that the site had two building phases. In the first phase, 510±20 BC, the internal structures were erected and aligned. In the second phase, 340±20 BC, the elliptical enclosure was built and aligned. An innovative application of Bayes’ theorem allowed us to estimate the probability that the enclosure was dimensioned by a priestess; this probability was found to be (55±8)%. This suggests that, with a probability of (72±8)%, there were both male and female druids (in the same sense as in the rest of Celtic Europe?) in Cisalpine Gaul. More significantly, we found out that the Bayes factor, estimated to be greater than ~(5.7±0.8) according to the Kass-Raftery scale, suggests that the structures provide “more than substantial” evidence for the presence of druidesses in Cisalpine Gaul.